UKRAINE ON THE WAY TO THE EUROPEAN SOCIAL STANDARDS: PROBLEMS AND PERSPECTIVES - Ярова, Л.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the given article new tendencies of social politics in the contemporary world are analyzed. The composition of subjects of social politics is clarified. The essence of social politics as a government activity and other social institutions in social sphere is examined. Clarify such notions of social politics as “social function of government”, “social quality”, „social indicators”, „social standards”. The role of non-commercial sector in social politics is shown.